Sustainable development goals and economic growth - Khushboo Kumari (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The Sustainable Development Goals (SDGs), adopted by the United Nations in 2015, provide a universal blueprint for achieving economic growth that is socially inclusive and environmentally sustainable by 2030. This paper examines the critical relationship between economic growth and sustainable development, focusing on how the SDGs serve as guiding principles for balancing economic expansion with social equity and environmental protection. Traditional economic growth models, often driven by resource-intensive industries and short-term gains, have led to environmental degradation and increased social inequalities. The SDGs call for a paradigm shift toward growth that promotes decent work, innovation, and infrastructure (Goal 8) while addressing poverty (Goal 1), inequality (Goal 10), and climate action (Goal 13). Sustainable economic growth emphasizes the importance of investing in human capital through education and healthcare, adopting clean and affordable energy solutions, and encouraging inclusive industrial development. These strategies contribute to resilience and long-term prosperity, ensuring that economic benefits are shared equitably across societies. However, achieving these goals presents challenges, especially for developing countries that face resource constraints and competing priorities.